(untitled) (Al-Academy, 2016)
The problem with research in the question of whether art forms in the religious icon Byzantine, heiress docility and tradition craftsman arts civilizations of the above? ... And if you are well, you helped a quotation on the entry of strange ideas rampant within religious traditions, and are prompted to do Movement rejected prohibition, and the outbreak of the icons war? ... Or is it, in fact - and as researcher finds - the result of a need communication between the religious and the recipient organization in the establishment of a deliberative speech, be visible, along with reading it and audible? .. And lies the importance of this study is being added technical knowledge of the library that will enrich researchers and scholars in this field and students of art colleges and institutes, interested in studying the history of art, and painting iconic in the Middle Ages in particular. The second chapter is divided into three Investigation; accept the first of the formal output of the Byzantine icon, the second section about art schools Byzantine icon. The third, in the terms of reference of examining a Byzantine icon. In the third chapter was selected models are deliberate analysis where adopted the descriptive analytical method, and of which there were three samples after the completion of the analysis the researcher to a range of outcomes, including: tends general approach toward simplification and reduction, after it was with the beginnings of a realistic then turned reported in maturity toward abstraction. Also characterized by a relatively small sizes, and repeating the first school model. Embodied the eastern Byzantine icon of theological thought (Orthodox). Sticking Almusbandh.jmoud manner of expression in specific templates. And get away and be careful not to highlight the details of the naked body. In addition to not - or scarcity - the use of popular iconography Palmruyat subjects